GREEN ACCOUNTING MEETS CSR: EXPLORING THEIR IMPACT ON SUSTAINABLE DEVELOPMENT IN INDONESIA'S PALM OIL COMPANIES - Yunita Sarah Siregar; Lailan Syafrina Hasibuan; Syafrita Ridha Ginting (CV. Radja Publika, 2025)
This study investigates the interplay between green accounting practices, corporate social responsibility (CSR), and sustainable development within Indonesian palm oil companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The primary objective is to determine the impact of green accounting on sustainable development, with CSR functioning as an intermediary. Utilizing path analysis and the Sobel test to evaluate mediation, the findings reveal a significant negative relationship between green accounting and CSR, potentially attributable to an imbalance in prioritizing environmental metrics over social initiatives. Conversely, CSR demonstrates a significant positive influence on sustainable development; however, it fails to mediate the relationship between green accounting and sustainability. The research underscores the necessity of aligning green accounting with CSR strategies to achieve sustainable development objectives. It also emphasizes the importance of active stakeholder engagement and periodic evaluations to devise more effective strategies for sustainability in Indonesia's palm oil sector.